2014
DOI: 10.1007/8904_2014_346
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function in Adults Aging with Fabry Disease: A Case–Control Feasibility Study Using Telephone-Based Assessments

Abstract: We examined the feasibility of recruiting US adults !45 years old with Fabry disease (FD) for telephone assessments of cognitive functioning. A case-control design matched each FD participant on age, sex, race, and education to four participants from a populationbased study. Fifty-four participants with FD age 46-72 years were matched to 216 controls. Standardized cognitive assessments, quality of life (QOL), and medical histories were obtained by phone, supplemented by objective indices of comorbidities. Norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…Some studies did not find significant differences between attentional performances in Fabry patients and healthy controls (Low et al 2007;Elstein et al 2012;Sigmundsdottir et al 2014;Lohle et al 2015), but all these studies but the one by Sigmundsdottir et al (2014) used cognitive screening tests and therefore may not have had the adequate diagnostic sensitivity. In accordance with our results, some studies found impairments in executive functions in Fabry disease (Segal et al 2010;Longato et al 2011;Sigmundsdottir et al 2014;Wadley et al 2015), whereas others did not. This may be because that the disease affects only specific executive functions or that different aspects of executive functions are impaired in different patients.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Some studies did not find significant differences between attentional performances in Fabry patients and healthy controls (Low et al 2007;Elstein et al 2012;Sigmundsdottir et al 2014;Lohle et al 2015), but all these studies but the one by Sigmundsdottir et al (2014) used cognitive screening tests and therefore may not have had the adequate diagnostic sensitivity. In accordance with our results, some studies found impairments in executive functions in Fabry disease (Segal et al 2010;Longato et al 2011;Sigmundsdottir et al 2014;Wadley et al 2015), whereas others did not. This may be because that the disease affects only specific executive functions or that different aspects of executive functions are impaired in different patients.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of previous studies of cognitive functioning in Fabry disease has found that cognitive deficits do occur in this patient group (Low et al 2007;Segal et al 2010; Longato et al 2011;Schermuly et al 2011;Elstein et al 2012;Sigmundsdottir et al 2014;Wadley et al 2015). Only one study found no significant difference in cognitive tests when comparing performances of patients with Fabry disease to performances of healthy controls (Lohle et al 2015).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations